Application Cases of Main Tourist Destination Competitiveness Models in Different Countries of the World, Especially in Balkan Region Destinations - Berdo, Sonila (European Journal of Multidisciplinary Studies, 2016)
The aim of this paper is to bring into consideration and describe the application of some of the main tourist destination competitiveness models implemented in different countries of the world and especially in Balkan region destinations. Destinations like Croatia, Romania, Bulgaria, Italia, Slovenia and some other wellknown like Taiwan, Caribbean islands and Sinaloe-Mexico are included in this study. The above cases are part of a literature review process related to this topic. These cases highlight the technical profile of the models and do contribute to facilitate the selection and implementation process of the appropriate model in similar countries or destinations not yet implemented. Different researchers of the field may provide a good understanding of the current tourism competitiveness situation in the regions here included and also of the way tourism competitiveness models needs to adapt to the study objectives and specific circumtainces of each case/ destination.